(untitled) (Al-Mansour Journal, 2023)
The state practices diplomatic protection for their citizens’ s if they are exposed to damages and cannot obtain Compensation by the normal way in this case the state interferes to obtain suitable compensations from the responsible state . the fundamental basis in diplomatic protection is that it’s practiced by diplomats after making certain that the basic conditions for protection like nationality, exhausting legal procedures and the plaintiff’s proper conduct but the consular officer only protect citizens of his state in certain case, and with certain right like entrance and leaving the country, the personal right and financial right.